A Grounded Theory Approach in Understanding the Experiences and Dilemma of Non-Readers in Basic Education - Marife A Abejuela; Alberto D Yazon; Lerma P Buenvinida; Karen A Manaig; Marcial M Bandoy (Research Synergy Foundation, 2025)
Over the past few years, a reading problem still exists despite the different reading programs and projects implemented all over the Philippines. None of the implemented programs tells what teachers, parents, and school administrators must do to uplift students’ reading skills. As stated in the DepEd Order no. 001 s. 2024, the Department’s current initiatives aim to improve learners’ academic performance, especially considering the low reading proficiency levels indicated by national and international large-scale assessments. These results highlight the urgent need to address learning gaps and enhance reading skills for all students. This study aimed to understand the experiences and dilemmas of non-readers in basic education in the Schools Division of Calamba City. The study applied a qualitative research design and followed the grounded theory research process. The researcher conducted face-to-face interviews to gather information on six (6) pupils from Grade 4 from two different public schools in the Division of Calamba City. A face-to-face interview was conducted to gather data from the participants over two weeks. The first round of interviews per participant lasted for 12-15 minutes and was recorded using a mobile phone. A second round of interviews was conducted with the participants to determine whether any patterns in their demographic profile could impact their reading abilities. Our findings showed that parental involvement and teacher support were the most crucial aspects to overcome absenteeism, a problem that mostly hampered reading performances for non-readers in context. Thus, Educational leaders must provide the support system needed by schools and communities to meet the expectations of providing literate learners. Developing countries like the Philippines need a holistic approach from the community, school, and education leaders to fully establish the desired goals of the new MATATAG agenda of the Department of Education.